A standardization method to disentangle environmental information from axial trends of xylem anatomical traits. (9th October 2018) - Lechthaler, Silvia; Turnbull, Tarryn L; Gelmini, Ylenia; Pirotti, Francesco; Anfodillo, Tommaso; Adams, Mark A; Petit, Giai
Abstract: Anatomical traits such as xylem conduit diameter and vessel connectivity are fundamental characteristics of the hydraulic architecture of vascular plants. Stem xylem conduits are narrow at the stem apex, and this confers resistance to embolisms that might otherwise be induced by large, negative water potentials at the top of tall trees. Below the apex, conduits progressively widen and this characteristic minimizes effects of path length on total hydraulic resistance. While interconnections among xylem vessels have been noted for decades, their role(s) are not fully clarified. For example, we do not know if they allow water to bypass embolized vessels, or increase the risk of spread of embolisms, or how their arrangement varies within a tree. Here we demonstrate the benefit of removing the independent effect of stem length on assessment of effects of external (e.g., climatic) factors on such xylem traits. We measured the hydraulic diameter (Dh) and vessel conductivity index (VCI) along the stem of 21 shrubs/trees of similar height (1.19 < H < 5.45 m) belonging to seven Acacia species, across a wide aridity gradient in Australia. All trees showed similar scaling exponents of Dh ( b = 0.33) and VCI ( b = 0.53) vs axial distance from the apex ( L ), thus conforming with general patterns in woody plants. After de-trending for L, neither Dh ( P = 0.21) nor VCI ( P = 0.109) differed across the aridity gradient. We found that across a wide gradient of aridity, climate had no effect on xylem anatomy of Acacia spp, which was instead dictated by axial distances from stem apices. We argue that the use of standardization procedures to filter out intrinsic patterns of vascular traits is an essential step in assessing climate-driven modifications of xylem architecture.